Cellular Regulation of Fibrinolysis - Plow, Edward F; Felez, Jordi; Miles, Lindsey A (Thrombosis and Haemostasis, 1991)
By virtue of their capacity to bind plasminogen activators and plasminogen, to accelerate plasminogen activation and to protect bound plasmin from inactivation by α2 antiplasmin, cells can harness the broad proteolytic activity of plasmin to their surface. Most cells bind plasminogen with a very high capacity, a relatively low affinity (Kd~1 εM) and recognize the lysine binding sites of the molecule. Gangliosides serve as non-protein plasminogen binding sites, and a subset of membrane proteins with carboxy-terminal lysine residues also serve as receptors. The alpha isoform of enolase possesses a carboxy-terminal lysine and is a prominent plasminogen binding protein of cells. Cells of the monocytoid lineage, including peripheral blood monocytes, can markedly upregulate their expression of plasminogen receptors. The capacity to modulate expression of receptors for fibrinolytic components establishes an additional mechanism by which the cell-surface regulates the function of the plasminogen system.